The relevance of Elvan Silva’s architectural discourse (ARQUISUR Revista, 2023)
This article addresses the architectural design process by exploring different theoretical and practical perspectives. It analyzes issues such as user participation, the relationship between theory and practice, the pursuit of a universal architectural language, and the importance of theoretical grounding and practical experience through the contributions made by architect Elvan Silva, theorist Christopher Alexander, and architect Le Corbusier. Additionally, elements such as contextualization, aesthetics, sustainability, and accessibility in the development of significant architectural projects are discussed. The article highlights the dynamic and interconnected nature of the design process, emphasizing the importance of continuous dialogue among the involved parties. The ultimate aim is to create architectural spaces that meet the needs and aspirations of people while becoming harmoniously integrated into the urban context
Keywords: architecture; architectural project; education and culture; teaching architecture